THE USAGE OF ENGLISH SONGS AND MUSIC AS PEDAGOGICAL TOOLS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE CONTEXTS - Rakhmonova Shakhnoza (Journals Park Publishing, 2023)
It is common to use music as one of the strategies in teaching English language for different ages. Teachers all over the world consider that music is really important tool in development of various aspects of the language such as vocabulary, pronunciation, listening skills and even it can act as a source of motivation for students to learn the target language in the EFL classrooms. However, there is still a lack of theoretical and practical researches in this sphere. This research paper is aimed to discuss opinions about the impact of songs on learning and teaching English language, besides that suggests ways of using this method. The author shares her observation, researches experiments, results and discoveries in this article.